2014
DOI: 10.1097/moh.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Global assays of hemostasis

Abstract: Purpose of review There exists an imbalance between our understanding of the physiology of the blood coagulation process and the translation of this understanding into useful assays for clinical application. As technology advances, the capabilities for merging the two areas have become more attainable. Global assays have advanced our understanding of the dynamics of the blood coagulation process beyond end point assays and are at the forefront of implementation in the clinic. Recent findings We will review r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 102 publications
(84 reference statements)
1
53
0
15
Order By: Relevance
“…Возможным решением являются интегральные или глобальные тесты гемостаза [1][2][3], которые ими-тируют патофизиологические процессы с большей точностью, позволяя оценить потенциал системы ге-мостаза в целом. В этих тестах обычно используются низкие концентрации активаторов (тест генерации тромбина, тромбоэластография) или активаторы, ло-кализованные на поверхности (тромбодинамика, про-точные камеры).…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified
See 2 more Smart Citations
“…Возможным решением являются интегральные или глобальные тесты гемостаза [1][2][3], которые ими-тируют патофизиологические процессы с большей точностью, позволяя оценить потенциал системы ге-мостаза в целом. В этих тестах обычно используются низкие концентрации активаторов (тест генерации тромбина, тромбоэластография) или активаторы, ло-кализованные на поверхности (тромбодинамика, про-точные камеры).…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified
“…Важной модификацией метода АЧТВ является так называемый анализ формы сигнала сгустка (clot waveform analysis), в котором анализируется вся кривая изменения оптической плотности, а не только время свертывания. Такую модификацию, в отличие от обычного теста АЧТВ, однозначно относят к гло-бальным тестам [1][2][3]. В частности, появление двух-фазной кривой в этом методе оказалось чувствитель-ным и специфичным ранним признаком развития ДВС (85 % и 92 % соответственно) [12].…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified
See 1 more Smart Citation
“…Studies in the healthy population have shown that thrombin generation dynamics differ largely between individuals, but are relatively stable over time in a given individual, supporting the concept that they may have utility as a phenotypic marker 25, 26, 27. The mechanism‐based bridge between thrombin generation assays and individualized risk prediction is plasma composition–based computational modeling 28, 29. Recently, computational models that kinetically describe the tissue‐factor initiated coagulation process (extrinsic pathway) have been utilized to define an individual's thrombin phenotype based upon their individual plasma composition of pro‐ and anticoagulant factors 30…”
Section: Introductionmentioning
confidence: 98%
“…One is to quantify the activation peptide released from prothrombin upon activation by factor Xa (F1+2 fragment) and the thrombin antithrombin complex. The other is to quantify the amount of thrombin that can be generated ex vivo by the addition of a small amount of trigger (usually tissue factor) to a plasma sample: the endogenous thrombin potential [26] . The analysis of thrombin generation is usually done with platelet-poor plasma, although the method can be modified to test plateletrich plasma.…”
Section: Thrombin Generationmentioning
confidence: 99%